PERBANDINGAN NILAI OVERALL EQUIPMENT EFFECTIVENESS (OEE) MESIN PACKER LAMA DAN MESIN PACKER BARU PADA PACKING PLANT INDARUNG (PPI) PT. SEMEN PADANG - Riko Ervil (Sekolah Tinggi Teknologi Industri Padang, 2016)
Packing Plant Indarung PT. Semen Padang which located at Jl. Raya Indarung - Padang has an important role to packing the cements. There are two types packer machines on Packing Plant Indarung, it is old packer machine and new packer machine. The objective of this study was to determine the effectiveness comparative of both packer machine types. One of method to measuring effectiveness machine is Overall Equipment Effectiveness (OEE). OEE is composed of three factors, that is Availability, Performance, and Quality. OEE score obtained by multiplying these factors.Result of the research show that Overall Equipment Effectiveness value of the new packer machines is higher than old packer machines. OEE score of the new packer machines is 69,14%. While OEE score of the old packer machines is 76,80%. Therefore, it was concluded that the effectiveness of new packer machine is better than old packer machine.Key Word : OEE, Packing Plant Indarung, PackerMachine, PT. Semen Padang